Vitamin D in overweight and obese children and adolescents: an integrative review (Research, Society and Development, 2020)
Obesity and vitamin D deficiency are prevalent problems worldwide, and are apparently related to each other, although the mechanisms of cause and effect of this combination are still unknown. This study aimed to highlight through a literature review the relationship between vitamin D and overweight and obese children and adolescents. This is a literature review of the narrative type, for its construction we used the following databases: Scielo, VHL and Google Scholar. Given the important role played by vitamin D in the human body, in addition to its relationship with chronic noncommunicable diseases, as well as the increased prevalence of overweight and obesity due to inadequate diet in the childhood and adolescent life cycles. , it is necessary to develop research of this nature, since there is a lack of studies on the theme